2018
DOI: 10.1155/2018/6375713
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pain Invisibility on Patient-Centered Care and Empathetic Attitude in Chronic Pain Management

Abstract: Objectives The use of interdisciplinary patient-centered care (PCC) and empathetic behaviour seems to be a promising avenue to address chronic pain management, but their use in this context seems to be suboptimal. Several patient factors can influence the use of PCC and empathy, but little is known about the impact of pain visibility on these behaviours. The objective of this study was to investigate the influence of visible physical signs on caregiver's patient-centered and empathetic behaviours in chronic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
14

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 43 publications
2
25
0
14
Order By: Relevance
“…For example, a study in Canada found that PCC and empathy from providers can positively affect patient health behaviors. 29 It is reported in the Netherlands that PCC has positive impact on patient satisfaction and well-being. 30 A study in Taiwan reported that patient autonomy and information preferences matter for the association between PCC and patient–provider relation and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study in Canada found that PCC and empathy from providers can positively affect patient health behaviors. 29 It is reported in the Netherlands that PCC has positive impact on patient satisfaction and well-being. 30 A study in Taiwan reported that patient autonomy and information preferences matter for the association between PCC and patient–provider relation and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of inflammatory arthritis (IA) (rheumatoid arthritis [RA] or spondyloarthritis [SpA]), especially pain or fatigue, are not always visible and are unpredictable, which has specific consequences, especially on relationships with others . In these diseases, help in physical tasks and emotional and social support are crucial, and adjustment to the disease necessarily implies adjustment for those who live close to the person .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of stigma experiences may include when individuals living with pain feel guilty about their physical limitations due to comments they receive from others, or when people in their circle doubt the reality of their pain (Eaves et al, 2015;Jackson, 2005;Pryma, 2017). Chronic pain is an invisible and subjective condition that can defy medical explanation, which may help to explain why people living with pain encounter such stigma and disbelief (Boulton, 2019;Joachim & Acorn, 2000;Lonardi, 2007;Paul-Savoie et al, 2018;Pryma, 2017;Quintner, 2020). The use of prescription opioid analgesics is another major source of stigmatization for people living with chronic pain, as these medications have increasingly been associated with stigmatized images of addiction and illicit drugs (Buchman et al, 2016;Eaves, 2015;Jackson, 2005;McCradden et al, 2019).…”
Section: Introductionmentioning
confidence: 99%